Effects of Linearly Polarized Near-Infrared Irradiation Near the Stellate Ganglion Region on Pain and Heart Rate Variability in Patients with Neuropathic Pain. Issue 3 (22nd July 2016) - Liao, Chun-De; Rau, Chi-Lun; Liou, Tsan-Hon; Tsauo, Jau-Yih; Lin, Li-Fong
Abstract: Background. Neuropathic pain associated with sympathetic overactivity can be effectively relieved by light irradiating the region near stellate ganglion (SGI), applied as an alternative to a conventional sympathetic blockade. The clinical effect of SGI on heart rate variability (HRV) and its association with pain outcomes require investigation. Objective. This study attempted to identify the effects of SGI on pain outcomes and HRV indices and to determine the association between pain and HRV outcomes. Design. A prospective double-blind, randomized study. Setting. An outpatient pain medicine clinic. Subjects and Methods. A total of 44 patients were enrolled and randomized into the experimental group ( n = 22) and control group ( n = 22). The experimental group received 12 sessions (twice weekly) of standard SGI, whereas the control group received the same protocol with sham irradiation. Pain and HRV were measured before and after each irradiation session. All outcome measures used in the first- and second-half treatment courses were analyzed. Results. Pain and HRV outcome measures of the experimental group significantly improved after SGI when compared with the control group in both courses. Considering time and frequency domains, the changes in HRV in the second-half treatment course exceeded those in the first-half treatment course. Pain was significantly associated with postirradiated HRV indices ( P < 0.001). Conclusions. Twelve sessions of SGI exerted time-dependent positive effects on pain and sympathovagal imbalance. HRV outcomes, including time and frequency domains, were an independent indicator of the clinical efficiency of SGI for treating pain in patients with neuropathic pain.